Variability of the precipitation over the Tianshan Mountains, Central Asia. Part II: Multi-decadal precipitation trends and their association with atmospheric circulation in both the winter and summer seasons - Guan, Xuefeng; Yao, Junqiang; Schneider, Christoph (Humboldt-Universität zu Berlin, 2021)
The annual precipitation over the Tianshan Mountains experienced an inter-decadal transition shift towards an increasing trend in the late 1980s. This study conducts attribution analysis from atmospheric circulation factors based on the Global Precipitation Climatology Centre (GPCC) dataset and NCEP/NACR reanalysis data. The results show that (a) Winter precipitation in the Tianshan Mountains is affected by multi-decadal oscillations with periods of 26.8 and 44.7 years, and has entered a period of positive anomalies after 1988. Although the non-linear trend of winter precipitation in the Tianshan Mountains firstly increased and then decreased after 1979, the multi-decadal fluctuation of precipitation caused the Tianshan Mountains in winter to be in a wet period from the 1980s until 2011. (b) We find that the East Atlantic-West Russia (EATL/WRUS) teleconnection pattern has a similar multi-decadal variability as Tianshan precipitation in winter. The wet period of Tianshan in winter after 1988 is mainly due to the enhanced meridional feature of the EATL/WRUS triggering more water vapour flux from low-latitude oceanic areas. (c) Summer precipitation in the Tianshan Mountains has an obvious multi-decadal scale of 33.5 years and shows a non-linear growth trend. Tianshan Mountains in summer entered a humid period after 1986. (d) The Scandinavia (SCAND) teleconnection pattern represents important circulation variability affecting Tianshan summer precipitation. The vigorous high pressure over the Ural Mountains and the low pressure over Central Asia during the SCAND negative phase in summer jointly lead to enhanced moisture transport from the Arctic Ocean to the Tianshan Mountains. (e) Apart from SCAND, the Silk Road pattern (SRP) and East Asia-Pacific teleconnection (EAP) also impacted Tianshan summer precipitation during the periods 1964–1984 and 1985–2004. Peer Reviewed